Screening for microsatellite instability identifies frequent 3'-untranslated region mutation of the RB1-inducible coiled-coil 1 gene in colon tumors. - Bogdan C Paun (Public Library of Science (PLoS), 2009)
Background Coding region microsatellite instability (MSI) results in loss of gene products and promotion of microsatellite-unstable (MSI-H) carcinogenesis. Recent studies have indicated that MSI within 3'-untranslated regions (3'UTRs) may post-transcriptionally dysregulate gene products. Within this context, we conducted a broad mutational survey of 42 short 3'UTR microsatellites (MSs) in 45 MSI-H colorectal tumors and their corresponding normal colonic mucosae. Methodology/principal findings In order to estimate the overall susceptibility of MSs to MSI in MSI-H tumors, the observed MSI frequency of each MS was correlated with its length, interspecies sequence conservation level, and distance from some genetic elements (i.e., stop codon, polyA signal, and microRNA binding sites). All MSs were stable in normal colonic mucosae. The MSI frequency at each MS in MSI-H tumors was independent of sequence conservation level and distance from other genetic elements. In contrast, MS length correlated significantly with MSI frequency in MSI-H tumors (r=0.86, p=7.2x10(-13)). 3'UTR MSs demonstrated MSI frequencies in MSI-H tumors higher than the 99% upper limit predicted by MS length for RB1-inducible coiled-coil 1(RB1CC1, mutation frequency 68.4%), NUAK family SNF1-like kinase 1(NUAK1, 31.0%), and Rtf1, Paf1/RNA polymerase II complex component, homolog (RTF1, 25.0%). An in silico prediction of RNA structure alterations was conducted for these MSI events to gauge their likelihood of affecting post-transcriptional regulation. RB1CC1 mutant was predicted to lose a microRNA-accessible loop structure at a putative binding site for the tumor-suppressive microRNA, miR-138. In contrast, the predicted 3'UTR structural change was minimal for NUAK1- and RTF1 mutants. Notably, real-time quantitative RT-PCR analysis revealed significant RB1CC1 mRNA overexpression vs. normal colonic mucosae in MSI-H cancers manifesting RB1CC1 3'UTR MSI (9.0-fold; p = 3.6x10(-4)). Conclusions This mutational survey of well-characterized short 3'UTR MSs confirms that MSI incidence in MSI-H colorectal tumors correlates with MS length, but not with sequence conservation level or distance from other genetic elements. This study also identifies RB1CC1 as a novel target of frequent mutation and aberrant upregulation in MSI-H colorectal tumors. The predicted loss of a microRNA-accessible structure in mutant RB1CC1 RNA fits the hypothesis that 3'UTR MSI involves in aberrant RB1CC1 posttranscriptional upregulation. Further direct assessments are indicated to investigate this possibility.